CHARACTER BUILDING THROUGH HADITH PERSPECTIVE (STUDY ANALYSIS ABOUT HADITH IMAN, ISLAM, AND IHSAN) - Ahmad, La Ode Ismail; Amri, Muhammad; Mosiba, Risna (Jurnal Diskursus Islam, 2019)
Character building is seen to be an essential answer of the grim value ofeducation in which the gap is occured between intelectual intelligence and socialintelligence. On the intelectual intelligence side, education system succesfulydelivers brilliant people. Meanwhile, on the social intelligence, some of those whoare educated regarded the education as a showcase to justify actions that actuallyadverse the commonsense. This is, of course, go against the true value of eductionin which the outcome is to shape a brilliant, well-mannered generation. This is alsocompatible with the mission of Prophet Muhammad who aimed to complete themorality of human being. Therefore, teachers as the primary key of education bear ahuge responsibilites to transfer all the knowledge to the learners according to Iman, Islam, and Ihsan philosophy. All can be done as the teachers become role models of Iman (faith), Islam (religious), and Ihsan (good behaviour) to their pupils in theirlearning process